Zonation and distribution of crabs in Pichavaram mangrove swamp, southeast coast of India - Ravichandran, S; Soundarapandian, S; Kannupandi, T (Indian Journal of Fisheries, 2011)
The zonation and distribution of crabs were studied in Pichavaram mangrove swamp. The season-wise distribution of crab species was maximum among the managal trees, especially Rhizophora and Avicennia species and open mud flats with mixed forests. Twenty three species of crabs were recorded from the mangrove. The species richness of crabs was higher in creek mangrove vegetation than in fringe mangrove types. Comparisons showed that the species composition of the crabs in the Sesarma zone was widely varied when compared to other Cardisoma, Ocypoda, Uca in mixed zones. More population and high species composition were recorded in the postmonsoon period. Each zone exhibited in characteristic species diversity. Distribution and zonation of crabs were based on the substratum, water level and floral distribution.